Константин Фофанов. Несколько замечаний по поводу его стихотворной техники (Konstantin Fofanov. Some Observations on His Verse Technique) - Egeberg, Erik (Poljarnyj vestnik, 2001)
In his time, Konstantin Fofanov (1862-1911) was a very popular poet, especially so in the late 80-s and early 90-s. His verse is clearly influ- enced by Afanasij Fet, although Fofanov lacks the emotional intensity of that poet. In this respect he is closer to Fet's contemporary Jakov Po- lonskij; both poets' verse contains dissonant elements which do not allow the rising emotional excitement to reach its potential climax. In the paper some of Fofanov's best poems are compared with those of Afanasij Fet.